Peranan Gereja dalam Sistem Pemerintahan yang Baik di Indonesia - David Ming (JURNAL KADESI, 2021)
The relationship between the church and a good goverment a very important matter to be discussed both in the academic sphere and in the scope of society in general. The relationship differs from time to time because the relationship between the two causes polemics. This is due to the understanding of the field that the ministry of the church should be limited to theological matters. On the other hand, there are those who argue that church activities cannot be narrowed down to only abstract/theological matters. Instead, the church must show concern for its concern for very concrete social issues, such as how to build good governance. From the results of this discussion, it was found that the Church must continue to provide color in Indonesian politics by continuing to provide inspiration in the midst of a pluralistic society in this nation.